MANFAAT PELAKSANAAN “DIPLOMASI WARGA” DI INDONESIA - Setyasih Harini (Jurnal Studi Diplomasi dan Keamanan, 2016)
This article discuss how diplomacy has been conducted by the increasing participation of the public in diplomatic activities. Coomunication technology can wider opportunity of citizen to make relations with another. In practice citizen diplomacy could not be easily differentiated from public diplomacy. Both of them still involvement of non-state actors (person, organization or public community) to increase the credibility of state’s diplomacy. Participation of citizen to make relationship with another from other countries also increase understanding each national identity. Citizen diplomacy still sees the participation of the public to support the government’s diplomacy. There are five typology of citizen diplomats from Paul Sharp to identify actors in citizen diplomacy and their forms of participation. Impact of this citizen diplomacy was very useful to developing countries. To sum up of this article, citizen diplomacy can be a method in conducting international relations through three criteria: participation of citizen, complementary to statebased diplomacy and requires non-state actors’ posession of global awareness.